DNA-based computing of strategic assignment problems - Shu, Jian Jun (2011)
DNA-based computing is a novel technique to tackle computationally difficult problems, in which computing time grows exponentially corresponding to problematic size. A strategic assignment problem is a typical nondeterministic polynomial problem, which is often associated with strategy applications. In this Letter, a new approach dealing with strategic assignment problems is proposed based on manipulating DNA strands, which is believed to be better than the conventional silicon-based computing in solving the same problem.